The long-range cytotoxic effect in tumor-bearing animals - Gerashchenko, B.I.; Ryabchenko, N.M.; Glavin, O.A.; Mikhailenko, V.M. (Experimental Oncology, 2012)
Aim:The relationship between cancer and patient health is still of great interest for experimental and clinical oncology. The tumor can adversely affect surrounding and distant tissues as well. However, effects of the tumor on distant tissues are much less studied than its effects on surrounding tissues. This study was aimed to test whether the tumor could trigger cytotoxic and/or genotoxic signals with respect to the distant proliferative tissue such as bone marrow. Materials and Methods: Rats were subcutaneously implanted with Guerin carcinoma cells, and on the 12th and 18th days after implantation both cytotoxic and genotoxic effects were assessed by flow cytometry in acridine orange stained unfractionated bone marrow cells isolated from femur. The cytotoxic effect was assessed using ratios of the following cell populations: total nucleated cells (TNC)/total enucleated erythrocytes (TE); polychromatic erythrocytes (PCE)/normochromatic erythrocytes (NCE). The genotoxic effect was assessed by quantification of micronucleated PCE (MNPCE) within the population of PCE. Results: A significant cytotoxic effect was observed in tumor-bearing animals on the 12th and 18th days after implantation (≈ 2-fold decrease in both TNC/TE and PCE/NCE ratios compared with corresponding parameters in control animals). There was also a genotoxic effect in these animals (a slight increase in the number of MNPCE), however, this effect was insignificant. The PCE/NCE ratio reversely correlated with the tumor weight which is suggestive of the link between erythropoietic cytotoxicity and tumor progression. Conclusion: Cytotoxic insult to the bone marrow is likely to be associated with the mechanism(s) triggered by distantly located tumors whose growth may correlate with the cytotoxic effect.